2019
DOI: 10.1042/bsr20190352
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dexmedetomidine on kidney injury of parturients with preeclampsia undergoing cesarean section: a randomized controlled study

Abstract: The present study aimed to elucidate the effects of dexmedetomidine on kidney injury of parturients with preeclampsia (PE) undergoing cesarean section. Total 134 cesarean delivery women with PE were randomly divided into intervention group (IG) and control group (CG). Both groups underwent combined spinal and epidural anesthesia (CSEA), the IG was treated with 0.4 μg/(kg·min) dexmedetomidine for 10 min before surgery. The CG was treated with equivalent saline. Heart rate (HR), blood pressure, oxygen saturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that administration of dexmedetomidine provided a significant hemodynamic stability during cesarean section in patients with preeclampsia [ 24 28 ]. There is very little published research on administration of dexmedetomidine for postoperative sedation of preeclampsia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that administration of dexmedetomidine provided a significant hemodynamic stability during cesarean section in patients with preeclampsia [ 24 28 ]. There is very little published research on administration of dexmedetomidine for postoperative sedation of preeclampsia patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,19 In addition, it has certain organ protective effects in subjects with preeclampsia, pulmonary hypertension in pregnancy and hyperthyroidism. [20][21][22][23] It is possible that these properties can be beneficial to the intraoperative and postoperative safety of caesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine can be administered both intravenously and intrathecally in obstetric anaesthesia 16–18 to optimize anaesthesia, reduce intraoperative stress and adverse reactions and ensure the safety of the infant and breastfeeding 7,19 . In addition, it has certain organ protective effects in subjects with preeclampsia, pulmonary hypertension in pregnancy and hyperthyroidism 20–23 . It is possible that these properties can be beneficial to the intraoperative and postoperative safety of caesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“… 137 It is also reported that dexmedetomidine exerts protective effects on kidney injury of parturients with preeclampsia undergoing cesarean section. 138 An assessment of its effect on both the mothers and neonates during cesarean section under general anesthesia indicates that dexmedetomidine presents better neonatal Apgar scores, postoperative analgesia, and decreased catecholamine release. 139 Moreover, the use of dexmedetomidine in the perioperative period of cesarean section is not only conducive to the early conversion of infant feeding to exclusive breastfeeding but can also enhance the recovery quality and comfort of the parturient, optimize analgesia, reduce the time to the first lactation, and increase lactation.…”
Section: Key Surgical Applicationsmentioning
confidence: 99%